OS TRANSPARENTES: UMA PROPOSTA INTERPRETATIVA - Oliveira, Mariel Mendes de (2018)
The novel Transparent city (2013) by Ondjaki brings Luanda as theme scenario, it has already received two awards and it also has been translated into five languages. The narrative deals with Odonato’s character story transparency process and it happens in the most part of the time in a building located in the downtown of the capital Angola, where some residents and their families, of plural familiar structures, share joys and sorrows. This thesis has a goal to analyze the book Transparent city underneath the interpretative perspective proposed by Roberto Schwarz in Duas meninas (1997). Schwarz has identified that the book Dom Casmurro (1899), by Machado de Assis, request three consecutive readings. Therefore, the researcher has verified the modes how some readers, in different historical contexts, have received the book. Based on these theoretical backgrounds we propose a reading of the novel based on alreadyread concept by Jameson (1992). On the first reading, considered Romanesque, we can observe the tragic end that some residents of Luanda due to because of a huge fire caused by a petrol company’s irregular excavations. On the second reading, of social nature, we are across from a society historically marked by power disputes among different classes and it tries day after day to rebuild itself in the midst of the chaos. On a third reading, we observe a turnaround in the narrative’s critical reception, in which the negative side of the social relations in Angola comes up in the novel. And Odonato’s transparency becomes symbolic, because, the narrative always shows the reader besides what it apparently says. This Master’s Degree thesis is divided into three parts, it starts by the critical essays on the author, and then, it exposes the theoretical perspective of the research, and lastly, it is proposed the novel’s reading supported by Schwarz’s interpretative model. This way, having into account the Schwarz’s interpretative model and other readings of the novel, we obtain advantages of this interpretation in order to show a countercurrent reading of this novel.